The Development of Food Finder Mobile Application - Soo, Sin Yee; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2022)
Food finder mobile application is developed to solve the indecisive problem of the foodies when they want to make a decision for daily meals. The proposed application provides the information and review of the foods to assist the users to make a better decision for their daily meals. Methodology used to develop this application is agile methodology. Food finder mobile application can reduce purchasing doubts, improve decision making and increase the probability of selecting satisfactory foods. This application is expected to provide guidance for the users to choose and decide for daily meals.